Functional asymmetries of hemispheres and perception of odours - Bratko, Denis; Barušić-Meglaj, Teuta (2002)
The purpose of this study was to explore the hemispheric differences in odour discrimination. The sample consisted of 89 participants. All of them were female and right-handed. Odours quality discrimination was tested with twelve pairs of odours presented to each nostril of every participant. The half of participants had odours presented to their left nostril first ("left-right" group), while the other half had them presented to their right nostril first ("right-left" group). The data was analysed in order to compare the efficiency of odour discrimination of left and right nostril. The analyses were carried out on the whole sample, as well as on the "left-right" and "right-left" sub-groups separately. For the whole sample, the difference between average scores for left and right nostrils didn't reach statistical significance. However, the "left-right" group showed clear right nostril advantage for discrimination of odours. In the "right-left" group there was no significant difference between nostrils.
Projekt MZOS
ENG